DEVELOPMENT OF ENTREPRENEURSHIP IN SURKHANDARYA REGION DURING THE YEARS OF INDEPENDENCE (Scientific journal of the Fergana State University, 2024)
This article shows the importance of entrepreneurship in ensuring the development of the state and the well-being of the people. In the Surkhandarya region, which is the southernmost region of our country, the reforms implemented in the field of entrepreneurship development over the years of independence were analyzed based on the principle of historicity.